SYSTEM OF USING PEDAGOGICAL TECHNOLOGIES IN TEACHING STUDENTS TO CRITICAL THINKING (British Journal of Global Ecology and Sustainable Development, 2023)
This article discusses the main content of teaching students to think critically - developing their independence, creativity, competence and research skills.